Point of Diagnosis and Patient Retention in HIV Care in Western Kenya. (1st August 2018) - Genberg, Becky L.; Lee, Hana; Hogan, Joseph W.; Some, Fatma; Wachira, Juddy; Wu, Xiaotian K.; Braitstein, Paula
Abstract : Background: Home-based counseling and testing (HBCT) achieves earlier HIV diagnosis than other testing modalities; however, retention in care for these healthier patients is unknown. The objective of this study was to determine the association between point of HIV testing and retention in care and mortality. Setting: Academic Model Providing Access to Healthcare (AMPATH) has provided HIV care in western Kenya since 2001. Methods: AMPATH initiated HBCT in 2007. This retrospective analysis included individuals 13 years and older, enrolled in care between January 2008 and September 2016, with data on point of testing. Discrete-time multistate models were used to estimate the probability of transition between the following states: engaged, disengaged, transfer, and death, and the association between point of diagnosis and transition probabilities. Results: Among 77, 358 patients, 67% women, median age: 35 years and median baseline CD4: 248 cells/mm 3 . Adjusted results demonstrated that patients from HBCT were less likely to disengage [relative risk ratio (RRR) = 0.87, 95% CI: 0.83 to 0.91] and die (RRR = 0.65, 95% CI: 0.55 to 0.75), whereas those diagnosed through provider-initiated counseling and testing were more likely to disengage (RRR = 1.09, 95% CI: 1.07 to 1.12) and die (RRR = 1.13, 95% CI: 1.06 to 1.20), compared with patients from voluntary counseling and testing. Once disengaged, patients from HBCT were less likely to remain disengaged, compared with patients from voluntary counseling and testing. Conclusions: Patients entering care from different HIV-testing programs demonstrate differences in retention in HIV care over time beyond disease severity. Additional research is needed to understand the patient and system level factors that may explain the associations between testing program, retention, and mortality.